O-005 YI Microbiota Drives Inflammation by Altering Intestinal Lamina Propria Macrophage Phenotype in a Novel IL10R-Deficient Model of Very Early Onset IBD. (March 2016) - Redhu, Naresh; Shouval, Dror; Bakthavatchalu, Vasudevan; Wang, Chuanwu; Conaway, Evan; Goettel, Jeremy; Mack, Matthias; Bleich, Andre; Bry, Lynn; Fox, James; Snapper, Scott; Horwitz, Bruce
Abstract : Background: Rare mutations in IL-10 or its receptors (IL10R) lead to severe very early onset (VEO)/infantile IBD in humans suggesting that the IL10/IL10R pathway is indispensable for mucosal immune homeostasis in the developing gut. Mice deficient in IL10/IL10R also develop spontaneous colitis. We recently reported that IL10R signaling in macrophages is critical for mucosal homeostasis in adult mice and humans (Shouval et al, Immunity 2014). However, the identification of IL10-dependent regulatory mechanisms in infants remains elusive. The goal of this study is to dissect key IL10R-dependent mechanisms that initiate mucosal homeostasis in the maturing infant colon. Methods: We performed age-dependent analysis of pro- and anti-inflammatory genes expression in the colon of developing littermate Il10rb −/− and Il10rb +/− (control) 129SvEv mice. We analyzed fecal microbiome from 2 to 14 week old control and Il10rb −/− mice using 16S rRNA sequencing. Flow cytometry was performed to assess various lamina propria (LP) immune cell populations. Antibiotics were given in drinking water starting in utero to investigate the influence of microbial communities on gene expression, LP immune populations, and inflammation. The role of pro-inflammatory macrophages (Ly6C +, CCR2 + ) in the development of pro-inflammatory signatures was assessed employing a CCR2-depleting antibody. Finally, we analyzed the development of colitis in crosses between C57BL/6 mice lacking IL10Rα and those carrying a genetic locus driving colitis susceptibility, Cdcs1, neither of which independently develop colitis in infancy. Results: Colitis was observed as early as 4 weeks in Il10rb −/− 129SvEv mice. An increase in colonic IL-10 expression was observed in both Il10rb −/− and control mice during the third week of life, and interestingly this was accompanied by a dramatic increase in proinflammatory cytokine expression including IL12p40, IL17A, and IFNγ within Il10rb −/− but not control mice. Increases in pro-inflammatory cytokines were paralleled by the expansion of Ly6C + monocytes and decreases in anti-inflammatory Ly6C − macrophages within the LP. Fecal microbiome analysis demonstrated a significant increase in microbial diversity, and acquisition of Helicobacter sp. at 3 weeks of age. Interestingly, while antibiotic treatment of Il10rb −/− mice attenuated expression of proinflammatory gene expression and expansion of Ly6C + monocytes, depletion of Ly6C + monocytes with CCR2 neutralizing antibodies did not diminish pro-inflammatory gene expression. Finally, while IL10Rα-deficient mice on C57BL/6 background do not develop colitis, severe spontaneous colitis developed in Cdcs1 +/+ Il10ra −/− mice on the C57BL/6 background by 3 weeks of age. Conclusions: Microbial colonization induces effector proinflammatory gene expression in the developing colon that is controlled by a concomitant induction of IL10. While antibiotics inhibited both inflammatory gene expression and Ly6C + monocyte accumulation, depletion of these Ly6C + monocytes did not inhibit inflammatory gene expression suggesting an alternative source for inflammatory cytokines in this model. We hypothesize that microbial-dependent skewing of intestinal Ly6C − macrophages rather than accumulation of Ly6C + monocytes in the absence of IL10R may play a central role in driving colonic inflammation in neonates that lack IL10R. We suggest that further mechanistic studies using the described novel IL10R-deficient neonatal models may lead to novel insights into the pathogenesis of both neonatal and adult onset IBD.